Kombinasi Algoritma Cipher Block Chaining (CBC) dan Mars Pada Penyandian File PDF - Ridha Ismadiah; Muhammad Syahrizal; Putri Ramadhani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
In today's competitive environment allows humans to communicate and can exchange data information or files remotely. Therefore it is necessary to protect information. One way that can be done is to exchange information in the form of Portable Document Format (PDF) files. The development of science that is very fast now causes information to be very valuable, therefore protection of information is needed. In this study combining two algorithms between algorithms namely Cipher Block Chaining (CBC) and Mars algorithms. To build this computerized application using Visual Basic 2008 as its supporting application. This application is made for the implementation of encryption and description of text files as secure communication.